Study of Behavioral Physiology of Mulberry Silk Moth: Exploring the Behavior and Physiology of Mulberry Silk Moths (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The homegrown silk moth, Bombyx mori, is a bug from the Bombycidae group of moths. The silkworm is a silk moth's hatchling or caterpillar. It is a creepy crawly of monetary essentialness, being an essential maker of silk. The behavioral physiology of the mulberry silk moth was examined in this study. During the most recent two days of pupal turn of events, incubating conduct was noted. Grown-up male and grown-up female conduct has been appeared to show fiery wing beating in the grown-up male, moving for lovemaking towards the female.